Bronchial provocation determined by breath sounds compared with lung function. Issue 8 (August 1991) - Noviski, N; Cohen, L; Springer, C; Bar-Yishay, E; Avital, A; Godfrey, S
Abstract : Bronchial provocation testing with methacholine was undertaken in 15 children aged 5 to 8 years with obstructive lung disease, mostly asthma (13/15). The methacholine was inhaled during two minutes of tidal breathing in increasing concentrations. After each inhalation, lung function was measured and clinical signs recorded independently by two observers unaware of each other's results. The logarithm of the concentration of methacholine which caused wheezing over the trachea correlated closely with the logarithm of the concentration of methacholine causing a 20% fall in the forced expiratory volume in one second (FEV1) but was 52% greater on average. At the end of the test there was a mean (SD) fall in FEV1 of 33.3 (7.4)% and a fall in oxygen saturation of 5.2 (3.1)%. Bronchial provocation testing by listening for wheeze over the trachea is a safe technique, which correlates with objective measures of lung function in young children.